Antara Eksklusif dan Pluralis: Rekonstruksi Narasi Kekristenan atas Agama Leluhur - Vikry Reinaldo Paais (Program Pascasarjana UKIM, 2022)
The relationship between Christianity and indigenous religion has been going on for a long time, but this relationship is not placed in the discourse of inter-religious relations. This is related to the paradigm and social construction in Christianity which has not fully recognized the indigenous religion as a